Refining Multilevel Barrier and Facilitator Measures for HIV Testing and PrEP Among Latino Sexual Minority Men - Lozano, Alyssa; Weinstein, Elliott R.; Fernandez, Alejandra; Bainter, Sierra; Atuluru, Pranusha; Hurtado, Abigail; Morales, Vanessa; Prado, Guillermo; Safren, Steve A.; Harkness, Audrey (American journal of health promotion, 2024)
Purpose The purpose of this study is to refine and establish measures of multilevel barriers and facilitators to HIV testing and PrEP for Latino sexual minority men (LSMM). Design Cross-sectional measure validation. Setting Participants from Miami, FL. Subjects 290 LSMM from the DÍMELO study. Measures Based on prior qualitative work, we developed two measures that evaluated multiple determinants (i.e., barriers and facilitators) to (1) HIV testing and (2) PrEP use. Analysis All measures included in this analysis assessed a set of theoretically distinct barriers and facilitators. We performed 11 exploratory factor analyses (EFA) to assess the dimensionality of theoretical groupings of items informed by prior qualitative work, including: knowledge, perceived need and benefit, mistrust and concerns, stigma and normalization, cultural competence, navigation support, provider demeanor, clinic and medical system issues, privacy concerns, cost, and language and immigration barriers. Based on EFA results, we conducted two confirmatory factor analyses (CFA), one for each measure. Results Within each measure, the 11 EFAs extracted 10 barrier factors and 7 facilitator factors. The CFAs for HIV testing and PrEP measures were consistent, such that all models retained the structures identified in the EFAs. Conclusion Findings support the use of these measures with LSMM. These measures can inform multilevel implementation strategies for health promotion professionals to scale up and disseminate HIV prevention services to LSMM.